Perceived Parental Behaviour and Religiosity as Predictors of In-school Adolescent Sexual Risk Behaviour in Ibadan Metropolis, Nigeria - Aderonke A. Akintola (Medical Science: Trends and Innovations Vol. 1, 2025)
Sexual risk behavior is an important contemporary concern, especially for the self-destruction and societal ills it causes. Research has been ongoing on adolescent sexual risk behavior in the country and recent studies still report high rates of pre-marital sexual activities among Nigerian adolescents. Sexual risk behavior among youth, defined as early sexual initiation, unprotected intercourse, or sex with multiple partners, is a major area of concern to parents or caregivers and health professionals given the many associated negative consequences. There is a dearth of literature on the interaction influence of perceived parental behavior and religiosity on adolescent sexual risk behavior in the country of Nigeria. This study, therefore, investigated the prediction of sexually risky behavior of the youth by their perception of their parental behaviors, and their religious belief. The roles of a few sociodemographic factors were also examined. A cross-sectional research design was employed. Using a multistage sampling technique, 1,589 participants, male (n=753), and female (n=836) aged 13 to 19 years were drawn from 10 private and 19 public secondary schools in three of the five Local Government Areas (LGA) in Ibadan Metropolis as participants for the study. Regression analyses revealed significant prediction by parental psychological control (\(β\)=.10, t=3.99, p<.01) while the other parental behavioral dimensions were not significant. Religiosity also significantly predicted sexual risk behavior among adolescents (F (1, 1584) =50.25, p<.001) (\(β\)=-0.18, t=-7.08, p<.001) indicating an increase in sexually risky behavior with a decline in religiosity. Age, Gender and family structure were also independent and significant predictors (\(β\) = 0.12, t=-4.89, p< 01; \(β\)= 0.30, t=-12.62, p<.01, \(β\) = 0.05, t=2.12, p<,05) respectively, implying the younger, male adolescents from polygamous setting are higher on sexual risk behavior. Implication is an overuse of psychological control. Efforts should be geared towards eliciting healthy parental behavior through teaching parenting skills and also giving adolescents cognitive therapy. Religiosity should also be encouraged.